LABORATORY MANAGEMENT SYSTEM SCHEDULING ASSISTANT INFORMATICS USING IN JAKARTA STMIK GREEDY METHOD - Rina Maylestari; Sahni Damerianta, SKom, MMSI Sahni Damerianta, SKom, MMSI (Jurnal Sistem Informasi, 2001)
This thesis describes the scheduling system at the laboratory informatics managementassistant at STMIK Jakarta, where the scheduling system is currently an assistantcarried out manually. assistant manually scheduling system has many weaknessesalthough there are advantages.authors tried to overcome the weaknesses of these systems with the proposed newsystem, namely assistant computerized scheduling system. if later found a weakness,chest charitable writer to accept. but of course the writer is attempting to design thesystem optimally scheduling the best assistant.way the system works can be seen in the discussion section, there are described indetail below design input and output. attached to the end writing the dialogue inputimage and the shape of the output along with the program, to support the proposednew system.